Book Review: J. Klewes, D. Popp and M. Rost-Hein (Eds), Out-thinking Organisational Communications: The Impact of Digital Transformation. (January 2018) - Bhalla, Bhavna
J. Klewes, D. Popp and M. Rost-Hein (Eds), Out-thinking Organisational Communications: The Impact of Digital Transformation, 2017, Switzerland: Springer International Publishing, 199 pp., €69, 99, ISBN: 978-3-319-41844-5 (Hardcover).